MACHINE ACCOUNTING IN THE ACCOUNTING CURRICULUM. - Graham, Willard J. (The Accounting Review, 1929)
A survey of current accounting practice indicates rather conclusively that a great majority of bookkeeping and accounting operations are performed with the aid of various types of mechanical equipment, commonly known as accounting machines. Broadly speaking, the term accounting machine. should include not only bookkeeping, analysis and tabulating machines, but also adding and calculating machines, cash registers, etc. Other office machines with important accounting applications, such as addressing machines and duplicating equipment, may also be included. Thus interpreted, the field covered is a very extensive one. The increasing volume of business transactions, the complexity of business organization, the growing necessity for delegation of responsibility and control all these factors have increased the dependence of the business man upon records and reports. Cost is an important factor in the preparation of such records and reports, hence the extent to which the necessary accounting and other clerical operations can be performed by mechanical means influences greatly the degree and type of managerial control which can be efficiently and economically exercised.